2008
DOI: 10.12693/aphyspola.113.1059
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Resistive Switching in Electrically Nonhomogeneous La0.67Ca0.33MnO3Thin Films by Short Electrical Pulses

Abstract: Resistance changes in thin electrically nonhomogeneous La 0.67 Ca 0.33 MnO 3 films were investigated using electrical pulses of nanosecond duration in the 80-300 K temperature range. Two types of reversible switching to higher resistive states with different starting temperature induced by series of the positive pulses were observed. Possible mechanisms of the resistance switching by short electrical pulses in the vicinity of Tm and at 80-90 K are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…3 by an arrow. Beginning stage of explanation of the switching near T m was presented in [12]. Extending these results we suppose that when the fields reach 10 kV/cm local heating of PM parts becomes apparent.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…3 by an arrow. Beginning stage of explanation of the switching near T m was presented in [12]. Extending these results we suppose that when the fields reach 10 kV/cm local heating of PM parts becomes apparent.…”
Section: Discussionsupporting
confidence: 54%
“…Fast cooling to ambient temperature also plays an important role in retaining of structural nonhomogeneities in thin films. Experimental results representing resistance switching, induced by pulsed thermocycling are presented in [12]. It was found that the duration of pulse in the series and temperatures runs during measurements plays an significant role on the results.…”
Section: Introduction *mentioning
confidence: 99%